Undergraduate Public Health Capstone Course: Teaching Evidence-Based Public Health - Fitzpatrick, Veronica Eileen; Mayer, Christen; Sherman, Barry R. (Frontiers in Public Health, 2016)
The University at Albany School of Public Health has offered a bachelor of science in public health (BSPH) degree for the past seven years. The final requirement of the BSPH degree is a capstone evidence-based public health class designed to cumulate the degree program. This capstone course is framed by identifying a public health problem and creating a literature review based on this problem. The issues are selected through collaboration between the students and instructors. Developmental and analytical tools necessary to complete the literature review are provided throughout the semester. By the end of the course students achieved the necessary competencies and skills to identify a public health problem, analyze information from peer-reviewed literature and synthesize the relationship between a health issue and its correlated outcome. Successes were measured through achievement of core BSPH competencies, quality of final paper and presentation, and qualitative data gleaned from end of semester self-reported student surveys.